Increasing cognitive learning and sports massage skills through a project-based blended learning model - Tisna MS, Gede Doddy; Suwiwa, I Gede; Yoda, I Ketut; Kusuma, Ketut Chandra Adinata (UIR Press Bekerjasama dengan International Association of Physical Education and Sports, 2024)
Background: Low achievement and poor learning skills among current students. Research Objectives: This research analysed the project-based blended learning model on cognitive learning achievement and sports massage skills. Methods: This research is a quasi-experiment. The population was 9 classes (180 students) in the Department of Physical Education. There were 4 classes (80 students) of the samples in this study. A random sampling technique was utilised in this study. A post-test-only control group design was used. Learning achievement was measured by multiple-choice tests, and the skills were measured by a massage skills test. The data were analysed using MANCOVA with SPSS at a 5% significance level. Finding/Results: The research finding showed that (1) there was a difference in massage learning achievement and massage skills between students who studied with project-based blended learning assisted by interactive multimedia and those with direct instruction with a significance number of 0.001 which is smaller than 0.05, (2) there was a difference in massage learning achievement between students who studied with project-based blended learning assisted by interactive multimedia and those with direct instruction, with a value of F = 8.400 and (3) there was a difference in massage skills between students who studied with project-based blended learning assisted with interactive multimedia and those with direct instruction, with a value of F = 13.817. Conclusion: It can be summarised that the project-based blended learning model could improve learning achievement and massage skills. The level of digital literacy has not been considered in this research; it is recommended that future research pay attention to this variable.